A probabilistic framework for assessment of reinforced concrete wall panel under cascaded post-blast fire scenario. (January 2022) - Roy, Tathagata; Matsagar, Vasant
Abstract: In a terrorist attack, structural elements such as, reinforced concrete (RC) wall panels have a relatively higher degree of exposure to blast loading which has the potential to trigger devastating fire hazard. As a result, there is significant limitation to the load carrying capacity of the structure, thereby leading to early collapse of structure. Therefore, to address this critical issue, a new probabilistic framework is developed and used to investigate reinforced concrete (RC) wall panels of different thicknesses exposed to cascading post-blast fire (PBF) scenario. The RC wall panels at elevated temperature after a random blast scenario are analyzed by nonlinear finite element (FE) approach considering material and geometric nonlinearities. The developed FE models for the RC wall panels are first exposed to uncertain blast scenario, and subsequently to random fire exposure. Uncertainties are considered in the capacity of structural members in terms of material strengths and heat transfer properties, and demand in terms of mechanical, blast, and fire loading. Response compared are in terms of deflection of the wall panels, variation of stresses at different interfaces, and damage pattern. It is concluded that the response under cascaded hazard involves significant damage to the RC wall panel, wherein the PBF requires ∼27%–∼35% less time to initiate failure, which is quite substantial considering the fire safety of structure. Further, the system uncertainty has significant influence on the duration of fire resistance of the RC wall panels under the PBF scenario. Finally, irrespective of the damaging concerns, it is suggested to use minimum panel thickness of 125 mm for ensuring fire protection of dwelling houses. Hence, in context to the current design guidelines, it is recommended to incorporate the effects of the cascading hazard scenario to protect the structures from extreme accidental/manmade threats. Highlights: A probabilistic framework is outlined to investigate the vulnerability of RC wall panels under post-blast fire. The RC panels under the PBF take ∼35% lesser time to initiate failure, which is important considering evacuation criteria. The fire resistance decreases by ∼11% – 23% for the RC panels under the cascaded hazard scenario. It is vital to consider uncertainty in the system and increased load of cascaded PBF to obtain reliable structural design.